2001
DOI: 10.1046/j.1442-9071.2001.00386.x
|View full text |Cite
|
Sign up to set email alerts
|

Periocular tumour of the follicular infundibulum

Abstract: Tumour of the follicular infundibulum (TFI) is an uncommon, benign lesion of the skin adnexae. Four cases are reported of periocular TFI. In all cases a clinical diagnosis of basal cell carcinoma was made before surgery; however, histopatholog ca examination revealed TFI. This is an epithelial tumour showing differentiation along the lines of the follicular infundibulum. Characteristic features are a shelf-like proliferat on of pale epithelia cells in the upper dermis, attachment to the epidermis and the upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Since the discovery of TFI in 1961, there have been many accounts of associated neoplasms ( Table I ). 9 , 13 , 14 , 15 , 16 , 17 , 19 , 20 , 21 One of the first mentions of TFI-associated lesions was in 1989, by Kossard et al. 6 In studying eruptive infundibulomas, they found that the platelike epithelial architecture of TFI was seen in association with seborrheic keratoses and BCC.…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of TFI in 1961, there have been many accounts of associated neoplasms ( Table I ). 9 , 13 , 14 , 15 , 16 , 17 , 19 , 20 , 21 One of the first mentions of TFI-associated lesions was in 1989, by Kossard et al. 6 In studying eruptive infundibulomas, they found that the platelike epithelial architecture of TFI was seen in association with seborrheic keratoses and BCC.…”
Section: Discussionmentioning
confidence: 99%